Influence of synthesis conditions on microstructure and phase transformations of annealed Sr2FeMoO6−x nanopowders formed by the citrate–gel method - Yarmolich, Marta; Kalanda, Nikolai; Demyanov, Sergey; Terryn, Herman; Ustarroz, Jon; Silibin, Maksim; Gorokh, Gennadii (Beilstein Journal of Nanotechnology, 2016)
The sequence of phase transformations during Sr2FeMoO6−x crystallization by the citrate–gel method was studied for powders synthesized with initial reagent solutions with pH values of 4, 6 and 9. Scanning electron microscopy revealed that the as-produced and annealed powders had the largest Sr2FeMoO6−x agglomerates with diameters in the range of 0.7–1.2 µm. The average grain size of the powders in the dispersion grows from 250 to 550 nm with increasing pH value. The X-ray diffraction analysis of the powders annealed at different temperatures between 770 and 1270 K showed that the composition of the initially formed Sr2FeMoO6−x changes and the molybdenum content increases with further heating. This leads to a change in the Sr2FeMoO6−x crystal lattice parameters and a contraction of the cell volume. An optimized synthesis procedure based on an initial solution of pH 4 allowed a single-phase Sr2FeMoO6−x compound to be obtained with a grain size in the range of 50–120 nm and a superstructural ordering of iron and molybdenum cations of 88%.
Keywords: magnetic materials; microstructure; nanoparticles; phase transformation; sol–gel preparation